PARADIGMA PENGEMBANGAN PERGURUAN TINGGI DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Arif Ismunandar (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2022)
Strengthening the field of technology in service and learning is part of the commitment of Higher Education administrators in creating a conducive and innovative lecture system supported by technology as a learning medium. Digital products are able to present scientific developments that are very fast and broad. Even this progress is accompanied by sophisticated technology. This is an opportunity for educational institutions to improve the quality and service of education which can show the face of the new education system both in the provision of quality infrastructure and superior and progressive human resources. in teaching more dominantly choose conventional learning methods rather than digital-based methods. The presentation of this paper is based on an analysis of library data with a descriptive analysis model. From the results of the discussion it can be concluded that Higher Education will be confronted by the Industrial Revolution Era 4.0. Education began to construct the existing system into a technology-centered system. Advances in digital technology in the era of the industrial revolution 4.0 will indirectly have an impact on the implementation of Islamic Higher Education. Procurement of technology directly can be said to have not been able to run smoothly. Budget/funding limitations are the main obstacle faced by every PTKIS, this will impact on the ability to procure learning support facilities and infrastructure. In addition, the obstacle faced is digital education. Lack of understanding of the use of digital media can make educators not have sufficient motivation in updating learning systems that are in line with the times.